Beyond Criminalization: Rethinking Same-Sex Sexual Offences and Punishment under Aceh’s Qanun Jinayat through Contemporary Maqasid al-Sharia’ah - Fines Fatimah; Madjid, Abdul; Chanifah, Nur; Liemanto, Airin (Brawijaya Law Journal, 2026)
This study examines the criminalization and punishment of same-sex sexual offences under Aceh’s Qanun Jinayat through the perspective of contemporary Maqashid al-Shari’ah. Using a qualitative approach with statutory, conceptual, and analytical methods, it explores the legal rationale underlying the criminalization of liwath and musahaqah as well as the punishment framework prescribed by Aceh’s Qanun. The study finds that Aceh's history is closely tied to its Islamic cultural values and the aim of implementing Islamic law based on regional autonomy. The criminalization stems from the view that liwath and musahaqah are prohibited by Islamic law, a stance established through ijtihad involving ulama and Qanun drafters. Applying Jazeer Auda's contemporary Maqashid al-Shari’ah framework, the study argues that both the scope of criminalized acts and the punishment system repuire critical reassessment to better fulfil the objecties of Islamic law in protecting human dignity, public welfare and social order. The study further proposes reconsiderations of the legal subject, the scope of criminal offences, alternative penal approaches, rehabilitative measures, and the regulation of organisational activities promoting same-sex sexual acts within Aceh’s Islamic legal framework.